Changing health behaviour of young women from disadvantaged backgrounds: evidence from systematic reviews. - Baird, J; Cooper, C; Margetts, B; Barker, M; Inskip, H (2009)
Observational evidence suggests that improving the diets of women of child-bearing age from disadvantaged backgrounds might be an important component of public health strategies aimed at reducing the burden of chronic disease in their offspring. The development of an intervention to improve the nutrition of young women needs to be informed by a systematic collation of evidence. Such a systematic collation of evidence from systematic reviews of interventions directed at changing health behaviours including diet, breast-feeding, physical activity and smoking has been conducted. Of 1847 potentially-relevant abstracts, fourteen systematic reviews met inclusion criteria. Four aspects of intervention design were identified that were effective at changing one or more of the health behaviours considered in the present review: the use of an educational component; provision of continued support after the initial intervention; family involvement; social support from peers or lay health workers. The findings of the present review suggest that interventions to change the health behaviour of women of child-bearing age from disadvantaged backgrounds will require an educational approach and should provide continued support after the initial intervention. Family involvement and social support from peers may also be important features of interventions that aim to improve diet.